Pullback attractors for a singularly nonautonomous plate equation - Carbone, Vera Lúcia; Nascimento, Marcelo José Dias; Schiabel-Silva, Karina; da Silva, Ricardo Parreira [UNESP] (My University, 2011)
We consider the family of singularly nonautonomous plate equation with structural damping utt + a(t, x)ut - Δut + (-Δ)2u + λu = f(u), in a bounded domain Ω ⊂ Rn, with Navier boundary conditions. When the nonlinearity f is dissipative we show that this problem is globally well posed in H2 0(Ω) × L2(Ω) and has a family of pullback attractors which is uppersemicontinuous under small perturbations of the damping a. © 2011 Texas State University - San Marcos.
Keywords: Nonautonomous system; Plate equation; Pullback attractor; Upper-semicontinuity